Molecular Cytopathology - Yang, Bin; Rao, Jianyu (Essentials in Cytopathology, 2016)
This book reviews the current application of molecular tools in cytopathology and serves as a concise handbook for those who provide care in this era of personalized medicine. Specifically, the text provides a comprehensive and concise review of the emerging molecular tests available clinically in different organ systems. It reviews the current data of molecular testing already applied in cytopathology, discusses some of the biomarkers with potential utility in cytopathology in the near future and reviews the technical challenges in applying and validating molecular tools in various cytologic materials. Molecular Cytopathology will serve as a valuable resource for cytopathologists, cytotechnologists, pathology trainees, and clinicians with an interest in molecular applications in cytopathology.